Canine pseudorabies - Schwalbe, Erin; Dorsch, Matías A.; Menk, Jose Cesar (Brazilian Journal of Veterinary Pathology, 2025)
A 3-year-old, female, Plott hound dog had a history of severe facial pruritus, swelling, and drooling. The week prior, this dog and three other dogs hunted feral hogs. At the time this dog was submitted for necropsy at the Louisiana Animal Disease Diagnostics Laboratory (LSU Diagnostics), the two other dogs had already died.